Performance of unique magnetic nanoparticles in biomedicine - Mansour Binandeh (Elsevier, 2022)
Much research has been done in the past on the use of nanoparticles in all biological and medical fields. One of the most important issues in this case is the use of nanoparticles (especially, magnetic nanoparticles) that have a suitable substrate surface for medical purposes. In the meantime, the size of the magnetic nanoparticles is very important and must be synthesized in a proper way. Our main goal is to use magnetic nanoparticles to absorb, stabilize and release drug biomolecules and to investigate all the effective factors to increase the quality of this operation. Past and recent studies in this field show the high and unique performance of magnetic nanoparticles for the mentioned purposes. With the spread of nanoscience in chemistry and its development in medicine, we can see a bright future for the purposeful transfer of biopharmaceuticals in the body of living organisms, especially humans.